Evaluasi Instalasi Pengolahan Air Minum Unit Dago Pakar Perumda Tirtawening Kota Bandung - Mayla Zahra Nugraha; Mohamad Rangga Sururi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Dago Pakar Water Treatment Plant (WTP) capacity600 liters/second, this WTP managed by Perumda Tirtawening Kota Bandung. It was established in 1990 and is still operating today. The main problem for water authority is the raw water quality of Cikapundung River deteriorated. This study refers to water quality compared with applicable regulations, design criteria based on literature, and evaluation of existing WTP using existing secondary data. The research shows some parameters were not meet the standard, there are several units that do not comply with the design criteria, and there are problems with the operation and maintenance of the Dago Pakar WTP. The causes of the existing problems are predicted based on activities carried out in the area around the Cikapundung River, namely the flushing of sewage, disposal of domestic waste, and the use of the river as a means of agricultural irrigation. Suggestions given regarding the problems that occurred were repairing the damaged Dago Pakar WTP equipment, adding sludge processing units such as sludge drying bed (SDB) and aeration units, tightening regulations for domestic or industrial waste disposal.